The dose-response relationship between BMI and hypertension based on restricted cubic spline functions in children and adolescents: A cross-sectional study - Wang, Yani; Min, Congcong; Song, Xiaoyan; Zhang, Heyue; Yuan, Chen; Chen, Lizhen; Zhang, Haiying (Frontiers in Public Health, 2022)
A high body mass index (BMI) is a major risk factor for hypertension. The purpose of this study was to investigate the association between the BMI and hypertension in children and adolescents in Qingdao, China. We analyzed data from 29,810 physical examinations in students aged 6–14 years old. A restricted cubic spline (RCS) function was used to investigate the dose–response relationship between the BMI and hypertension. The prevalence of hypertension was 9.91% in our sample, 11.71% in males and 7.9% in females. Compared to the normal weight group, the relative risk (RR) for hypertension in the overweight group was 1.729, and the RR for hypertension in the obesity group was 3.089. After adjusting for potential confounders, the adjusted odds ratios for the BMI–hypertension association were 1.561 [95% confidence interval (CI): 1.403–1.737] in the overweight group and 2.946 (95% CI: 2.686–3.231) in the obesity group. According to the multivariate RCS regression analysis, there was a significant nonlinear dose–response association between the BMI and the risk of hypertension (all P-values for nonlinear < 0.001). In addition, the dose–response relationship analysis showed that with a continuous change of BMI, the association strength of hypertension increased nonlinearly.